2008
DOI: 10.1016/j.ydbio.2008.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Growth of cranial synchondroses and sutures requires polycystin-1

Abstract: In vertebrates, coordinated embryonic and postnatal growth of the craniofacial bones and the skull base is essential during the expansion of the rostrum and the brain. Identification of molecules that regulate skull growth is important for understanding the nature of craniofacial defects and for development of non-invasive biologically based diagnostics and therapies. Here we report on spatially restricted growth defects at the skull base and in craniofacial sutures of mice deficient for polycystin-1 (Pkd1). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 48 publications
(46 reference statements)
3
54
0
Order By: Relevance
“…17 In our study, the hypoplastic maxilla and the subsequent skeletal Class III could be associated with the palatal tipping of the upper incisors we observed in the mutant mice. Based on the analysis of the skull phenotype observed in Pkd1-deficient mice, Kolpakova-Hart et al 17 hypothesized that tensile force within the growing viscerocranium is essential for skeletal growth and that PC1 is an important mediator of this process, as it controls proliferation of mesenchymal cells at the osteogenic fronts. Later on, Hou et al 18 demonstrated that these mutant mice exhibited an impaired response to tensile force.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…17 In our study, the hypoplastic maxilla and the subsequent skeletal Class III could be associated with the palatal tipping of the upper incisors we observed in the mutant mice. Based on the analysis of the skull phenotype observed in Pkd1-deficient mice, Kolpakova-Hart et al 17 hypothesized that tensile force within the growing viscerocranium is essential for skeletal growth and that PC1 is an important mediator of this process, as it controls proliferation of mesenchymal cells at the osteogenic fronts. Later on, Hou et al 18 demonstrated that these mutant mice exhibited an impaired response to tensile force.…”
Section: Discussionsupporting
confidence: 54%
“…Current studies [15][16][17][18][19] specific to the effect of primary cilia on skeletal growth and mechanical stress indeed showed promising results in support of the PC1 sensor role hypothesis.…”
Section: Introductionmentioning
confidence: 83%
“…PC1 is expressed in cells within the osteoblast lineage (18), and skeletal abnormalities have been reported in Pkd1 mutant mouse models (14,15,17,18), but from these generalized lossof-function observations it was not clear if the observed skeletal abnormalities were an indirect consequence of loss of PC1 in multiple tissues or a direct effect of loss of PC1 in osteoblasts. In the present studies, we have addressed this question by using mice had a ϳ25% reduction in Pkd1 expression, whereas Pkd1 flox/m1Bei mice had a 50% reduction but had identical effects on bone, suggests that loss of Pkd1 function in osteoblasts is responsible for the observed reduction in bone mass in both models.…”
Section: Discussionmentioning
confidence: 99%
“…Some genes and transcriptional factors specifically regulate neural crest proliferation and apoptosis: Prtg-deficient (protogenin protein) mice show malformation of bones due to increased apoptosis of rostral CNC (Wang et al, 2013). Polycystin-1 (Pkd1) is required for the proliferation of subpopulations of cranial osteochondroprogenitor cells of both mesodermal and neural crest origin during the growth of the skull (Kolpakova-Hart et al, 2008). Deficiencies of Msx1 and Msx2, homeodomain transcription factor, result in defective patterning and survival of the cranial neural crest (Ishii et al, 2005).…”
Section: Neural Crest Proliferation and Apoptosismentioning
confidence: 99%